Use of Molecular Methods for the Rapid Mass Detection of Schistosoma mansoni (Platyhelminthes: Trematoda) in Biomphalaria spp. (Gastropoda: Planorbidae) - Roberta Lima Caldeira; Liana Konovaloffi Jannotti-Passos; Omar Dos Santos Carvalho (Journal of Tropical Medicine)
The low stringency-polymerase chain reaction (LS-PCR) and loop-mediated isothermal amplification (LAMP) assays were used to detect the presence of S. mansoni DNA in (1) Brazilian intermediate hosts (Biomphalaria glabrata, B. straminea, and B. tenagophila) with patent S. mansoni infections, (2) B. glabrata snails with prepatent S. mansoni infections, (3) various mixtures of infected and noninfected snails; and (4) snails infected with other trematode species. The assays showed high sensitivity and specificity and could detect S. mansoni DNA when one positive snail was included in a pool of 1,000 negative specimens of Biomphalaria. These molecular approaches can provide a low-cost, effective, and rapid method for detecting the presence of S. mansoni in pooled samples of field-collected Biomphalaria. These assays should aid mapping of transmission sites in endemic areas, especially in low prevalence regions and improve schistosomiasis surveillance. It will be a useful tool to monitor low infection rates of snails in areas where control interventions are leading towards the elimination of schistosomiasis.